Anthocyanin-enriched purple sweet potato for colon cancer prevention - Lim, Soyoung (Kansas State University, 2012)
Anthocyanins are flavonoid pigments that account for the purple color in many plant foods. It has been investigated that anthocyanins’ predominant occurrences in human diet and their health beneficial activities such as antioxidant, anti-inflammatory, and anti-carcinogenetic effects. Based on those scientific evidences, anthocyanins are now recognized as potential therapeutic compounds. Particularly, the chemopreventive effect of anthocyanins has been widely studied by many researchers in nutrition. However, their bioactivities are diverse due to different chemical structures of anthocyanins from different sources. In this study, we discuss the chemopreventive activity of anthocyanins from purple sweet potato. Previously, we selected a purple-fleshed sweetpotato clone, P40, crossbred seeds obtained from the International Potato Center in Lima, Peru. We hypothesized that anthocyanins enriched P40 may provide health beneficial activities in cancer prevention. For the first part of this study, we analyzed nutrient compositions, dietary fiber content, anthocyanins contents, total phenolics contents and total antioxidant activity. Even thought P40 presents similar composition and amount of nutrients with the control cultivars, white-fleshed O’Henry and yellow-fleshed NC Japanese, HPLC-MS analysis confirmed that it possesses much higher anthocyanin content even up to 7.5g/kg dry matter. Also, dietary fiber, particularly soluble dietary fiber content, total phenolics content, and total antioxidant capacity of P40 were significantly higher. For the second part of the study, we tested the potential anticancer characteristic of P40 cultivar in human colonic SW480 cancer cells and in azoxymethane-induced aberrant crypt foci in mice. Treatment with 0 – 40 μM of peonidin-3-glucoside or P40 extract containing corresponding amount of anthocyanins resulted in inhibition of cell growth in a dose-dependent manner. Interestingly, even though the patterns of growth inhibition were similar in the two treatment groups, the cells treated with P40 extract tend to survive significantly less than those treated with peonidin-3-glucoside. Cell cycle analysis confirmed that the growth inhibition was not due to cytotoxicity, but cytostatic mechanism with increased number at the G1 phase of the cell cycle. The cell cycle arrest was also significantly correlated with the anthocyanin contents in P40 cultivar when compared with the white-fleshed O’Henry and yellow-fleshed NC Japanese controls. After Azoxymethane (AOM) or saline injected mice were fed basal AIN-93M diet or diets containing 10~30% of P40, 20% O’Henry or 20% NC Japanese for 6 weeks, aberrant crypt foci (ACF) multiplicity was significantly inhibited by 10~30% P40 diet. Imunohistochemistry results of colonic mucosa showed that the expression level of apoptosis marker, caspase-3, was significantly induced in the mice treated with 10~20% P40 diet. Also, PCNA expression level, which is proliferation marker, was significantly inhibited by the 30% P40 diet. These findings indicated that consuming a purple sweet potato, P40, may prevent colon cancer by modulating antioxidant status, inducing apoptosis, and reducing cell proliferation.
Keywords: Purple sweet potato; Colon cancer; Anthocyanins; ACF; Peonidin 3-glucose; SW480; Nutrition (0570)